Artificial Lighting System Design with PWM Control for the Growth of Kangkung Microgreen - Muhammad Fauzan; Syukriyadin Syukriyadin; Fahri Helta; Syahrizal Syahrizal; Alfisyahrin Alfisyahrin (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
Microgreen plants such as lettuce, spinach, and kangkung can be cultivated indoors, with artificial lighting like Light Emitting Diodes (LEDs) replacing sunlight. This study compared the growth of kangkung microgreens under artificial lighting using Pulse Width Modulation (PWM) versus without PWM. Two sample trays, each containing 50 grams of kangkung seeds, were placed 50 cm below the light. The first tray used PWM lighting, starting with a 65% duty cycle at 8 a.m, increasing to 100% by 12 p.m, and decreasing back to 65% by 4 p.m. The second tray received constant lighting without PWM. Results showed that PWM improved power efficiency from 16.3 W without PWM to 13.36 W with PWM. Growth of kangkung microgreens improved with PWM, evidenced by better stem length, leaf count, wet weight, stem diameter, petiole length, and leaf width, although single root length with PWM (9.68 cm) was slightly shorter than without PWM (9.98 cm).Base on statistical t-test results showed that there was a significant difference in stem length between lighting treatments using the PWM method and without using the PWM method, with a significance level of 5%. The study successfully developed an automated lighting control system using PWM that enhances plant growth. Keywords: Artificial lighting, Indoor farming, Kangkung, Microgreen, Pulse wave modulation.